Retórica da imagem: análise de uma campanha política - Bertolo, Fernando (2022)
This dissertation comprises a study linked to the Text and speech in oral and written modalities and conducts an analysis of two propaganda pieces of the political campaign of Guilherme Boulos as mayor of São Paulo in 2020. As mass media emerged, speeches composed of text and image began to be produced industrially. The image influences, moves, induces action. We may be attracted or repelled by it, but we are hardly indifferent to its provocation. The identification of the processes of production of meaning of images allows us to understand how to rhetorically analyze discourses composed of image and text. The corpus was chosen because it is inserted in a context of communication experimentation, as the covid-19 pandemic limited traditional campaign techniques. Our hypothesis is that there are several aspects in the images that contribute to the construction of the rhetorical proofs logos, ethos and pathos. In order to achieve the intended objective, we seek support in classical rhetoric and in the new mediated rhetoric to understand the reading of the image. As a method of analysis, this dissertation was based on bibliographical research and analysis based on Barthes's (1990) image reading categories with the rhetorical analysis script proposed by Galinari (2014). After the analysis, we believe that we have found different strategies for producing rhetorical evidence through images, in addition to having proved that classical rhetoric can be a discipline of analysis not only for textual discourses